Biodiversity of helminths in Karakul sheep in the Khorezm Oasis of Uzbekistan - A. A. Akbarov; F. J. Akramova; U. A. Shakarbayev; D. A. Azimov (Российский паразитологический журнал, 2023)
The purpose of the research is to study the helminth fauna and the structure of helminthocenoses of Karakul sheep in the Khorezm Oasis of Uzbekistan.Materials and methods. The material for this study was helminths collected by conventional methods from Karakul sheep from farms of different types in the Khorezm Region. A total of 13 sheep were studied. To identify the dominant helminth infections in sheep, 110 sets of individual organs were examined by the method of partial helminthological dissections. Helminths were collected in slaughterhouses of the Bagat, Kushkupyr, Urgench, Yangiaryk and Shavat Districts of the Khorezm Region. Additionally, the helminths collected from sheep in the Khorezm Region for 2015–2021 were used.Results and discussion. We found that the helminth fauna of Karakul sheep from the Khorezm Oasis was represented by 22 species of the classes Cestoda, Trematoda and Nematoda. Cestodes were represented by 6 species, trematodes by 3 species, and nematodes by 13 species. The faunistic composition of helminths in studied animals was noticeably depleted as compared to other Uzbekistan regions due to natural and ecological conditions of the Khorezm Oasis. The total helminth infection rate in sheep was 100%. The intensity of infection varied depending on the season of the year and the age of sheep and ranged from tens to several thousand specimens. Almost all organs and systems of the animals were found to be ecological niches of the above helminths. Most of helminth species were common to both domesticated and wild ungulates.